2015
DOI: 10.17554/j.issn.2313-3406.2015.02.13
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Epigenetic Modulation in the Cellular Response to Ionizing Radiation

Abstract: More and more evidence demonstrate that epigenetic modulation plays important roles in many cellular processes and carcinogenesis. It also showed that epigenetic changes are involved in the cellular response to ionizing radiation. In current review, we will discuss the radiation-induced epigenetic modifications including DNA methylation changes, chromatin remodelling and alterations in microRNA expression, and their roles in the cellular response to ionizing radiation. The aim is to help understand the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 104 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…2,26 Researchers have demonstrated that LDR-induced accelerated epigenetic changes include mi RNA expression that involved stimulating DNA repair, suppressing cell lethality, intercellular induction of apoptosis, and suppressing cancer progression. 28,29 In this study, we found that graviola treatment only (EG group) at a dose of 50 mg/kg body weight/day for 30 days or as an adjuvant with LDR (EGR group) at a dose level 2 Gy once a week for 3 weeks decreased tumor volume and inhibited tumor growth. According to a study on breast cancer, treatment with Annona muricata fruit extract for 5 weeks induced tumor regression.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…2,26 Researchers have demonstrated that LDR-induced accelerated epigenetic changes include mi RNA expression that involved stimulating DNA repair, suppressing cell lethality, intercellular induction of apoptosis, and suppressing cancer progression. 28,29 In this study, we found that graviola treatment only (EG group) at a dose of 50 mg/kg body weight/day for 30 days or as an adjuvant with LDR (EGR group) at a dose level 2 Gy once a week for 3 weeks decreased tumor volume and inhibited tumor growth. According to a study on breast cancer, treatment with Annona muricata fruit extract for 5 weeks induced tumor regression.…”
Section: Discussionmentioning
confidence: 65%
“…2,26 Researchers have demonstrated that LDR-induced accelerated epigenetic changes include mi RNA expression that involved stimulating DNA repair, suppressing cell lethality, intercellular induction of apoptosis, and suppressing cancer progression. 28,29…”
Section: Discussionmentioning
confidence: 99%
“…It includes a series of molecular modifications including chromatin remodelling, DNA methylation, histone modifications, genetic imprinting, X chromosome inactivation and noncoding RNA (LncRNA, miRNA and siRNA, etc) regulated gene expression [19]. DNA methylation is an important epigenetic modifications of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic alterations are a kind of heritable changes in gene transcription or expression mode by regulating genome's structure and function, while the DNA sequence itself do not change [ 18 ]. It includes a series of molecular modifications including chromatin remodelling, DNA methylation, histone modifications, genetic imprinting, X chromosome inactivation and noncoding RNA (LncRNA, miRNA and siRNA, etc) regulated gene expression [ 19 ]. DNA methylation is an important epigenetic modifications of the genome.…”
Section: Introductionmentioning
confidence: 99%